2006
DOI: 10.1099/mic.0.29137-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two-component signal transduction systems of Bacillus cereus, Bacillus thuringiensis and Bacillus anthracis

Abstract: Members of the Bacillus cereus group are ubiquitously present in the environment and can adapt to a wide range of environmental fluctuations. In bacteria, these adaptive responses are generally mediated by two-component signal transduction systems (TCSs), which consist of a histidine kinase (HK) and its cognate response regulator (RR). With the use of in silico techniques, a complete set of HKs and RRs was recovered from eight completely sequenced B. cereus group genomes. By applying a bidirectional best-hits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 89 publications
2
63
0
3
Order By: Relevance
“…Recovered sequences were further scrutinized according to the following criteria: (i) the HATPase domain had to be located in the C-terminus (last 2/3) of the encoded protein and (ii) a putative H-box had to precede the HATPase domain. Detection of HK-RR gene pairs and 'orphan' HK and RR genes was similar to that described previously [11].…”
Section: Identification Of Hks and Rrssupporting
confidence: 64%
See 1 more Smart Citation
“…Recovered sequences were further scrutinized according to the following criteria: (i) the HATPase domain had to be located in the C-terminus (last 2/3) of the encoded protein and (ii) a putative H-box had to precede the HATPase domain. Detection of HK-RR gene pairs and 'orphan' HK and RR genes was similar to that described previously [11].…”
Section: Identification Of Hks and Rrssupporting
confidence: 64%
“…Zhang was similar to that described previously [11]. Briefly, the HMM profile (Accession numbers PF00512) was found in Pfam database that targets the HisKA family of HKs, which was used to recognize the HKs in the L. casei genomes.…”
Section: Identification Of Hks and Rrsmentioning
confidence: 99%
“…Among the genes identified in this study, one (BC5440) was found to encode a protein of a two-component regulatory system that may function to sense and perceive the environment more precisely and respond to it. The BC5440 gene product does not belong to the same response regulator family as B. subtilis DesR (16). BC5440 encodes a response regulator probably involved in the regulation of enzymes with murein hydrolase activity (like regulators in the LytR/AlgR family) (24).…”
Section: Discussionmentioning
confidence: 99%
“…To map the occurrence of RsbK and RsbY homologues in other species, a similar approach was followed as described previously (de Been et al, 2006(de Been et al, , 2010. This approach included a straightforward BLAST search with the HK phosphotransferase (RsbK) and REC (RsbK and RsbY) domain sequences.…”
Section: Rsbk-type Hybrid Kinases Occur In a Wide Variety Of Bacteriamentioning
confidence: 99%